2022
DOI: 10.1590/1982-4327e3207
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Styles and Moral Emotions of Adolescents in Conflict with the Law

Abstract: The cognitive and emotional development of adolescents is affected by how they perceive their parents’ upbringing, or parenting style. This study aimed to verify the relationship between the perception of parenting styles by adolescents who committed transgressive acts and compare it to that of adolescents without such a history, also searching for associations with the moral emotions of pride, shame, and guilt. In total, 219 adolescents in conflict with the law and 243 non-offender adolescents participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
1
0
2
Order By: Relevance
“…Braga et al's (2017) meta-analysis on the relationship between maltreatment and adolescents' antisocial behaviors found that physical maltreatment by parents is related to violent delinquent behavior among adolescents. Also, parental verbal abuse tends to wound children's psyches so deeply that the effects remain apparent in young adulthood (Laskoski et al, 2022). Further study by Vallejo Valdivieso et al ( 2022) on the prevalence of child abuse and criminal behavior among 425 male adolescents in Ecuador confirmed a significant relationship between the abuse suffered during childhood and the criminal behavior reported.…”
mentioning
confidence: 93%
“…Braga et al's (2017) meta-analysis on the relationship between maltreatment and adolescents' antisocial behaviors found that physical maltreatment by parents is related to violent delinquent behavior among adolescents. Also, parental verbal abuse tends to wound children's psyches so deeply that the effects remain apparent in young adulthood (Laskoski et al, 2022). Further study by Vallejo Valdivieso et al ( 2022) on the prevalence of child abuse and criminal behavior among 425 male adolescents in Ecuador confirmed a significant relationship between the abuse suffered during childhood and the criminal behavior reported.…”
mentioning
confidence: 93%
“…En relación con este tema Diana Baumrind es una de las precursoras que argumenta que el comportamiento de los padres se basa en dos dimensiones fundamentales: aceptación y control; estas dimensiones se combinan para establecer tres estilos parentales que influyen en el comportamiento de los menores: autoritario, permisivo y autorizativo. Además de estos estilos, MacCoby y Martin agregaron el permisivo, señalando que los cuatro surgen de la combinación del afecto y el control que se brinda a los hijos (7) (8) (9).…”
Section: Introductionunclassified
“…Depois de Baumrind, outros pesquisadores deram seguimento aos estudos sobre os estilos parentais (Cassoni, 2013) e, ainda que o sistema proposto por Baumrind tenha continuado importante, a tipologia proposta por Maccoby e Martin (1983) ganhou notoriedade, pois permite uma maior generalização do modelo para populações diferentes daquela em que sua tipologia surgiu (Darling & Steinberg, 1993), favorecendo, por exemplo, estudos que investigam relações entre status socioeconômico (SSE) e estilos parentais (Hoff et al, 2002). (Laskoski et al, 2022).…”
Section: Estilos Parentais E Desenvolvimento Na Infância E Adolescênciaunclassified